The Guideline for Caring of Pregnant Women and Postpartum Women in the Post-Pandemic of the 2019 Novel Coronavirus Disease (COVID-19) - khamthanet, Rattanaporn; Arunyaphark , Pattaraporn (Journal of Nursing, Siam University, 2023)
Novel Coronavirus 2019 (COVID-19) is a new epidemic that is severely spread across the world. Its signs and symptoms look similar to influenza. People who get infected with COVID- 19 shall express mild to severe symptoms. Some patients have a fever (a high fever that lasts for 48 hours), dry cough, mucus cough, sore throat, headache, losing a sense of smell, tiredness, out of energy, getting exhausted, difficulty in breathing, etc. People at risk of COVID-19 are older adults, people with underlying diseases, people with overweight, including pregnant women. Infection in pregnant women is associated with an increased the risk of complications and higher severity of the disease. Getting infected with COVID-19 shall increase a risk of severe faire in the cardiac system and respiratory system. Besides, it shall affect undesirable symptoms during pregnancy such as preeclampsia, disseminated intravascular coagulation, preterm birth, or severe symptoms requiring treatments in the ICU, leading to death. Therefore, giving knowledge and self-care guidelines to pregnant women and postpartum women is highly important to reduce the spread of COVID-19 and the severity of the disease among them.